Functional Active Genomics of Isoprene Biogenesis and resistance to cardiovascular diseases - Fedoriv, Anna; Fedoriv, Ivan (Technium BioChemMed, 2021)
The pathologic development of the atherosclerotic process is often associated with the metabolism of saturated and unsaturated fatty acid. Substitution of the saturated fatty acids in nutrition for polyunsaturated fatty acids is traditionally associated with the lowering of risk of coronary breaches rise. Understanding the molecular mechanisms of the atherosclerosis development and progress is very important for early diagnostic and effective medical treatment of the above-mentioned disease. After a thorough analysis of the data available on the pathological atherosclerotic process, we have come to the conclusion that this disease begins from vascular smooth muscle cell (VSMC) impaired function. In the basis of the atherosclerosis development lies isoprenes biogenesis breach, caused by cholesterol and the products of its metabolism. Atherosclerosis is a chronic inflammatory disease of the media wall of large- and medium-sized arteries. And endothelium injury is a consequence of the pathologic process progressing in myocytes. Metabolic problems have become so relevant that it is time to form a metabolic policy. Real target programs for the prevention of the development of metabolic diseases and their diagnostics in the early stages of development should be developed. But in order to achieve this goal, it is necessary to know the real molecular mechanism of development of the early stages of metabolic diseases. It is necessary to recognize that the research work on the metabolic problem was carried out mainly in the plane of the functionally-energy parameter and captures only the consequences of the pathological process. And the very reason and early stages of metabolic diseases remained hidden from us, as they are depending on the pathology in the plane Regulatory, Information, Coordination and Functional active bioenergy system.